The Chandra Survey of the Small Magellanic Cloud "Bar". II. Optical Counterparts of X-ray Sources - Antoniou, V.; Zezas, A.; Hatzidimitriou, D.; McDowell, J. C. (The Astrophysical Journal, 2009)
We present the most likely optical counterparts of 113 X-ray sources detected in our Chandra survey of the central region of the Small Magellanic Cloud (SMC) based on the OGLE-II and Magellanic Clouds Photometric Survey catalogs. We estimate that the foreground contamination and chance coincidence probability are minimal for the bright optical counterparts (corresponding to OB type stars; 35 in total). We propose here for the first time 13 high-mass X-ray binaries, of which four are Be/X-ray binaries (Be-XRBs), and we confirm the previous classification of 18 Be-XRBs. We estimate that the new candidate Be-XRBs have an age of ~15-85 Myr, consistent with the age of Be stars. We also examine the "overabundance" of Be-XRBs in the SMC fields covered by Chandra, in comparison with the Galaxy. In luminosities down to ~1034 erg s-1, we find that SMC Be-XRBs are ~1.5 times more common when compared to the Milky Way even after taking into account the difference in the formation rates of OB stars. This residual excess can be attributed to the lower metallicity of the SMC. Finally, we find that the mixing of Be-XRBs with other than their natal stellar population is not an issue in our comparisons of Be-XRBs and stellar populations in the SMC. Instead, we find indication for variation of the SMC XRB populations on kiloparsec scales, related to local variations of the formation rate of OB stars and slight variation of their age, which results in different relative numbers of Be stars and therefore XRBs.
Keywords: Astrophysics; Be; Magellanic Clouds; pulsars: general; stars: early-type; stars: emission-line; stars: formation; X-rays: binaries